1970
DOI: 10.1080/00288233.1970.10421599
|View full text |Cite
|
Sign up to set email alerts
|

Ingested soil as a source of microelements for grazing animals

Abstract: Two sheep were drenched each with 100 g of soil containing approximately 1 mc each of 60Co, 540Mn, 75Se, and 65Zn. Activities of these isotopes in blood, urine, and faeces were monitored at intervals over a lO-day period by gamma-ray spectroscopy. At the end of this period the animals were killed and a range of hard and soft tissue samples was taken for analysis. From the data obtained on blood and tissue samples taken at time of death, and from urine samples over the lO-day period, amounts of isotopes absorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
1

Year Published

1976
1976
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 10 publications
0
23
1
1
Order By: Relevance
“…This ingested soil may serve as a source of essential minerals (Healy et al 1970, andSuttle 1974) like copper (Cu). For example, Stoszek (1976) observed that while three grass-fed cattle became severely Cu depleted, a fourth animal, which had the habit of eating soil, accumulated Cu.…”
mentioning
confidence: 99%
“…This ingested soil may serve as a source of essential minerals (Healy et al 1970, andSuttle 1974) like copper (Cu). For example, Stoszek (1976) observed that while three grass-fed cattle became severely Cu depleted, a fourth animal, which had the habit of eating soil, accumulated Cu.…”
mentioning
confidence: 99%
“…Em um animal que esteja ingerindo 3% do peso vivo de matéria seca e 10% do peso vivo de água, a presença de 150 ppm de Fe na água significa um acréscimo de 500 ppm na matéria seca. Por outro lado, outra fonte muito importante de Fe é o consumo de solo, que em algumas ocasiões, em bovinos, pode chegar a 600 kg por ano (Healy 1974). O maior consumo de solo ocorre quando há pouca disponibilidade de pastagens, o que é freqüente durante o inverno, na época em que se registram os surtos de morte súbita.…”
Section: Discussionunclassified
“…This figure is consistent with the dry matter intake for both horses and cattle (Dulphy et al 1992), which are the two species most commonly grazed on historic landfill in the UK. It is well attested that horses directly eat soil (McGreevy et al, 2001) and, like cattle, will also eat soil adhered to plant material (Healy, 1974). There are no clear figures for the amount of soil consumed by grazing horses, but figures for cattle range between 1.1 % and 4 % of dry matter intake under usual agricultural conditions (Thornton & Abrahams, 1983;Thornton, 2002).…”
Section: Discussionmentioning
confidence: 99%